SOSIALISASI PEMANFAATAN PEKARANGAN SEBAGAI TEMPAT BERCOCOK TANAM KELOMPOK WANITA TANI (KWT) DESA AMBARAWA (LP3K Lampung, 2021)
The women farmer group is an organization that actually exists, and functions as a vehicle for extension and activator of activities in their field. With this activity, of course, it can have a positive impact on the family economy. Farm women can help their husbands to earn income to meet their daily needs. Yard is open land or vacan land that is not maintained which is usually found around a residence. The yard can also provide us with tremendous benefits if we can cultivate it. Farming is cultivating a piece of land to cultivate and expecting the land to produce a harvest.